Chemical Composition and Biological Activity of Essential Oil from Cinnamomum Spp. and Litsea Spp. - Noor Fasihah, Binti Hasan (Universiti Malaysia Sarawak, UNIMAS, 2011)
The essential oils from the leaves, barks, stems and roots of Cinnamomum zeylanicum, Cinnamomum burmannii, Cinnamomum iners, Litsea gracilipes and Litsea resinosa was extracted using hydrodistillation method. The essential oil obtained was analyzed by Gas Chromatography-Mass Spectroscopy (GC/MS). The percentage yields of essential oil from Cinnamomum and Litsea species ranged from 0.01-3.72 %. The highest percentage was obtained from the leaves of C. burmannii while the lowest percentage of oil obtained from the stem of C. burmannii. The major chemical compositions in C. zeylanicum were eugenol, camphor, tetradecanal and cinnamyl acetate. The chemical compositions in the oils of C. burmannii were rich in benzyl benzoate, (+)-2-bormanone, tetradecanal and caryophyllene. C. iners was contained (+)-2-bormanone and hexadecanoic acid as the major compound. The chemical compositions in the oil of L. gracilipes were rich in caryophyllene, α-bisabolene and spathulenol while the oil of L. resinosa contained o-cymene, caryophyllene, epizonarene and 3-methylacetophenone as the major constituents. The toxicity and antitermite activities of the essential oils were determined. All the essential oil showed inhibitory activity against the larvae of Artemia salina with the LC50 value in the ranged of 3.02-56.23 μg/mL. The leaf oil of C. burmannii showed stronger biological activity against the larvae of A.salina and termites of Coptotermes sp. with LC50 values of 3.02 μg/mL and 100 % mortality after 3 days treatment at 1.0 % concentration respectively. Other essential oil from Cinnamomum spp. was exhibited moderately inhibitory activity towards termites Coptotermes sp. with 50-61 % mortality at 10 % concentration after 3 days of contact